Identification and Quantification of Transient Receptor Potential Vanilloid 1 (TRPV1) in Equine Articular Tissue - Anne Frank Gallagher vom Braucke (Animals, 2020)
Joint pain and osteoarthritis (OA) are some of the most common causes of lameness in horses, and most of the available treatments focus on symptomatic relief without a disease-modifying effect. TRPV1 is a potential target for treating joint diseases, including OA, and the present study aims to investigate if the TRPV1 receptor is present in equine articular tissue and determine whether the number of receptors is upregulated in joint inflammation. Metacarpo/metatarsophalangeal (MCP/MTP) joints from 15 horses euthanised for reasons unrelated to this study were included. Based on synovial fluid analysis, macroscopic evaluation, and magnetic resonance imaging (MRI), joints were divided into two groups: healthy joints and joints with pathology. ELISA analysis was performed on synovial tissue harvested from all joints. TPRV1 was found in all joints. The mean concentration of TRPV1 compared to total protein in healthy joints (8.4 × 10−7 ng/mL) and joints with pathology (12.9 × 10−7 ng/mL) differed significantly (p = 0.01, t-test with Welch correction). Quantitative real-time reverse transcriptase PCR analysis was performed on RNA isolates from synovial tissue from all joints. TRPV1 mRNA expression ratio normalized to glyceraldehyde 3-phosphate dehydrogenase (GAPDH) in healthy joints (0.16 (SD: 0.19)) and joints with pathology (0.24 (SD: 0.14)) did not differ significantly (p = 0.43, t-test with Welch correction). mRNA expression of interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF-α) was very low for both groups. In conclusion, TRPV1 was detected both on mRNA and the protein level, with a higher expression of TRPV1 in samples from joints with pathology. Future studies will determine the clinical potential of equine TRPV1 as a target in the management of joint pain and inflammation.